2004
DOI: 10.1080/07315724.2004.10719390
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Magnesium Supplementation in Patients with Type 2 Diabetes

Abstract: Effects of magnesium (Mg) supplementation on nine mild type 2 diabetic patients with stable glycemic control were investigated. Water from a salt lake with a high natural Mg content (7.1%) (MAG21) was used for supplementation after dilution with distilled water to 100mg/100mL; 300mL/day was given for 30 days. Fasting serum immunoreactive insulin level decreased significantly, as did HOMA squareR (both p < 0.05). There was also a marked decrease of the mean triglyceride level after supplementation. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 10 publications
1
45
1
3
Order By: Relevance
“…Recently, two cation channels of the transient receptor potential melastatin cation channel family have been identified as magnesium transporters and implicated as a signalling kinase involved in vascular smooth muscle cell growth, apoptosis, adhesion, contraction, cytoskeleton organization and migration, as well as important processes involved in vascular remodelling associated with hypertension and other vascular diseases. 29 The effect of magnesium supplementation on SBP and DBP in this study was higher than reported in previous studies using different magnesium salts, [9][10][11][12]30,31 but similar with a previous non-randomized study with MgCl 2 in which both SBP and DBP decreased significantly, by a mean of 13±9 mm Hg. 32 It has been reported that MgCl 2 shows a higher bioavailability than other commercial magnesium preparations, 21 circumstance that could be involved in a better response using this salt for magnesium supplementation.…”
Section: Magnesium and Hypertensioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Recently, two cation channels of the transient receptor potential melastatin cation channel family have been identified as magnesium transporters and implicated as a signalling kinase involved in vascular smooth muscle cell growth, apoptosis, adhesion, contraction, cytoskeleton organization and migration, as well as important processes involved in vascular remodelling associated with hypertension and other vascular diseases. 29 The effect of magnesium supplementation on SBP and DBP in this study was higher than reported in previous studies using different magnesium salts, [9][10][11][12]30,31 but similar with a previous non-randomized study with MgCl 2 in which both SBP and DBP decreased significantly, by a mean of 13±9 mm Hg. 32 It has been reported that MgCl 2 shows a higher bioavailability than other commercial magnesium preparations, 21 circumstance that could be involved in a better response using this salt for magnesium supplementation.…”
Section: Magnesium and Hypertensioncontrasting
confidence: 54%
“…In this regard, we conducted a randomized clinical trial that compared the effect of magnesium supplementation among hypertensive subjects receiving concurrent captopril; however, in other studies, the effect of magnesium supplementation has been evaluated in randomized clinical trials that compared magnesium versus placebo. [10][11][12][13]31 It has been suggested that magnesium may attenuate the biological actions of angiotensin II, 33 which inhibits norepinephrine release, 34 and that a direct calcium antagonist effect of magnesium at the cellular level might be involved in the BP effects of magnesium; 35 furthermore, it has also been reported that captopril increases cytosolic-free magnesium levels 36 and that the BP reduction with oral magnesium supplementation is significantly higher among patients with elevated levels of plasma rennin activity. 37 In this regard, it is possible that the greater reduction of BP that we observed could be related with a synergic action of MgCl 2 and captopril and/or that our patients have high levels of plasma rennin activity.…”
Section: Magnesium and Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical evidences of a clear effects of Mg supplements on the metabolic profile of diabetic subjects are controversial, benefits having been found in many [8,61,63,64], but not in all clinical studies [65].…”
Section: Mg Supplementation In the Prevention And Management Of Diabetesmentioning
confidence: 99%